2017
DOI: 10.1186/s12859-017-1810-x
|View full text |Cite
|
Sign up to set email alerts
|

Robust gene selection methods using weighting schemes for microarray data analysis

Abstract: BackgroundA common task in microarray data analysis is to identify informative genes that are differentially expressed between two different states. Owing to the high-dimensional nature of microarray data, identification of significant genes has been essential in analyzing the data. However, the performances of many gene selection techniques are highly dependent on the experimental conditions, such as the presence of measurement error or a limited number of sample replicates.ResultsWe have proposed new filter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Microarray techniques have increased the capability to explore the pathogenic processes of several diseases and represents an important technology for functional genomic studies [15,16]. Microarrays have been used detect certain RA-specific proteins, including anacardic acid, histone acetyltransferase, nuclear factor-kappa B, and prostaglandin D2 synthase [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Microarray techniques have increased the capability to explore the pathogenic processes of several diseases and represents an important technology for functional genomic studies [15,16]. Microarrays have been used detect certain RA-specific proteins, including anacardic acid, histone acetyltransferase, nuclear factor-kappa B, and prostaglandin D2 synthase [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the genome-wide DNA microarray based on high-throughput platforms for gene expression analysis, has emerged as an efficient and relatively economical tool to study complex disease genetics. [ 10 ] Therefore, we compared gene expression profiles in subcutaneous adipose tissue between OSA and control from the Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/geo ) for screening differentially expressed genes (DEGs). Subsequently, the DEGs were identified using a combination of functional enrichment and protein-protein interaction (PPI) analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the mechanism of genes and proteins correlation and key pathways in the pathogenesis of ICM are necessary to improve the prevention, diagnosis and treatment. Recently, with the continuous development of genomic technologies, microarray technology and RNA sequence have increased the ability of experts to investigate the genes regulation of cardiovascular disease (11). A few studies have reported that unique genes contribute to the pathogenesis of heart failure.…”
Section: Introductionmentioning
confidence: 99%